Evaluation of the Smoked Machine with Dual Heating Sources - Lidyana, Roslan; Annisa, Jamali; Rudiyanto, Philman Jong; Ana Sakura, Zainal Abidin; Abang Mohammad Nizam, Abang Kamaruddin; Rasli, Muslimen; Shahrol, Mohamaddan; Mohd Zulhatta, Kifli; Mohd Syahmi, Jamaludin (IEEE, 2022)
Abstract— This paper presents a design for a smoked machine that combines an insulated chamber with a heating filament, blowers, and a biomass smoking furnace. A combination of energy sources from heating filament and wood which was fed into the furnace at predetermined amounts were utilized to achieve the desired temperature. Temperature and airflow velocity in the chamber of the machine were simulated to elucidate the behaviour of hot air flow and observed the temperature difference at every point in the machine. The finite element analyses showed that there was a stagnant air pocket in the upper rear region of the chamber due difference in pressure at the inlet and outlet. Therefore, the design was optimized, and a rotating tray design was proposed for the pilot test machine. Then, a pilot test was carried out to verify the proposed design. The pilot tests were conducted using banana fish, which is a type of Albula vulpes species, weighing from 0.3–0.4 kg/head. It was observed that the temperature of the smoking chamber varied from 85ºC and 115ºC. The results showed that the smoking system was able to perform the smoking process of the fish in 3 hours with 50% moisture reduction and no coliform or e-coli were found in the samples. Based on the test results, the dual heating smoking system developed and evaluated in this study is predicted to be able to complete the smoking process of the fish in 4-5 hours with 70% moisture reduction which complies with food safety regulations. In addition, it has the capacity to produce hygienic smoked fisheries.